2023
DOI: 10.1371/journal.pone.0291361
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor and its correlation with estrogen and progesterone receptors, aimed for identification of cases for future anti-androgen therapy in endometrial cancers

Neda A. Moatamed,
Saba Vahdatshariatpanahi,
David W. Gjertson
et al.

Abstract: Introduction The expression of androgen receptor (AR) is not commonly tested or studied in uterine cancers, unlike estrogen receptor (ER) and progesterone receptor (PR) which are positive in most endometrial carcinomas. In this series, we evaluated the expression of AR and its comparison to ER and PR in different types of endometrial cancers and have reviewed the literature. Materials and methods The status of AR, ER, and PR expression were evaluated in 71 cases which were categorized into endometrial endome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(67 reference statements)
0
0
0
Order By: Relevance
“…Moatamed and colleagues evaluated androgen receptor expression in endometrial cancers and found that it was near ubiquitous in endometrial endometrioid cancers (EECs) and prevalent in about two-thirds of non-endometrioid endometrial cancers (NEEC) [ 16 ].…”
Section: Precision Medicine Genomics Microbiome and Immunological Bio...mentioning
confidence: 99%
“…Moatamed and colleagues evaluated androgen receptor expression in endometrial cancers and found that it was near ubiquitous in endometrial endometrioid cancers (EECs) and prevalent in about two-thirds of non-endometrioid endometrial cancers (NEEC) [ 16 ].…”
Section: Precision Medicine Genomics Microbiome and Immunological Bio...mentioning
confidence: 99%